The Usage Of Google Apps As Communication Tools A Case Study Of Senior High Schools In Jakarta - Deddy, Muharman (2022)
Technological developments in education are growing day by day. One of the advances is the use of applications in learning, where Google introduced a platform called Google for Education (GFE). However, in Indonesia, the use and adoption of these applications, notably Google for Education, is not smooth and evenly distributed. Apart from technical factors, non-technical factors such as teacher motivation and knowledge are the obstacles. This study tries to dig into these problems in three different high schools by using Yin’s single-embedded type case study analysis to investigate and explain three schools selected, and then try to compare the results to understand the difference. From the research results, it can be concluded that GFE use in certain subjects encountered technical difficulties due to compatibility with the applications previously used. And Google Classroom, as the mainly used Applications, became a mainstay application because it made students independent in learning without the need for a standby teacher. From three schools selected, SMA X is a school that is quite maximum in using and adopting GFE. The habit of using iPad as a learning medium and complete mastery of technology from its teachers are the reasons. Finally, theoretically it can be seen how to get maximum use and adoption, external issues remain an important apprehension